Effectiveness, safety and costs of the FreeStyle Libre glucose monitoring system for children and adolescents with type 1 diabetes in Spain: a prospective, uncontrolled, pre-post study - Lilisbeth Perestelo-Pérez; Amado Rivero-Santana; Cristina Valcárcel-Nazco; Yolanda Álvarez-Pérez; Pedro Serrano-Aguilar; Yolanda Ramallo-Fariña; Lidia García-Pérez; Miguel Angel García-Bello; Himar Gonzalez-Pacheco; Ariadna Campos Martorell; Amparo González Vergaz; Ana María Prado Carro; et al. (BMJ Open, 2023)
Objectives This study aimed to evaluate the effectiveness, safety and costs of FreeStyle Libre (FSL) glucose monitoring system for children and adolescents with type 1 diabetes mellitus (T1DM) in Spain.Design Prospective, multicentre pre-post study.Setting Thirteen Spanish public hospitals recruited patients from January 2019 to March 2020, with a 12-month follow-up.Participants 156 patients were included.Primary and secondary outcome measures Primary: glycated haemoglobin (HbA1c) change. Secondary: severe hypoglycaemic events (self-reported and clinical records), quality of life, diabetes treatment knowledge, treatment satisfaction, adverse events, adherence, sensor usage time and scans. Healthcare resource utilisation was assessed for cost analysis from the National Health System perspective, incorporating direct healthcare costs. Data analysis used mixed regression models with repeated measures. The intervention’s total cost was estimated by multiplying health resource usage with unit costs.Results In the whole sample, HbA1c increased significantly (0.32%; 95% CI 0.10% to 0.55%). In the subgroup with baseline HbA1c≥7.5% (n=88), there was a significant reduction at 3 months (−0.46%; 95% CI −0.69% to −0.23%), 6 months (−0.49%; 95% CI −0.73% to −0.25%) and 12 months (−0.43%; 95% CI −0.68% to –0.19%). Well-controlled patients had a significant 12-month worsening (0.32%; 95% CI 0.18% to 0.47%). Self-reported severe hypoglycaemia significantly decreased compared with the previous year for the whole sample (−0.37; 95% CI −0.62 to –0.11). Quality of life and diabetes treatment knowledge showed no significant differences, but satisfaction increased. Adolescents had lower sensor usage time and scans than children. Reduction in HbA1c was significantly associated with device adherence. No serious adverse effects were observed. Data suggest that use of FSL could reduce healthcare resource use (strips and lancets) and costs related to productivity loss.Conclusions The use of FSL in young patients with T1DM was associated with a significant reduction in severe hypoglycaemia, and improved HbA1c levels were seen in patients with poor baseline control. Findings suggest cost savings and productivity gains for caregivers. Causal evidence is limited due to the study design. Further research is needed to confirm results and assess risks, especially for patients with lower baseline HbA1c.